Peranan Lurah dalam Penyelesaian Sengketa Tanah di Kelurahan Wette’e Kecamatan Panca Lautang Kabupaten Sidenreng Rappang - Astinah Adnan; Ernawati Suherman (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
Abstract The goal of this research is to determine the role of village chief on unfinished land lawsuit settlement along with all influencing factors. This is seen as there are so many cases such as borderland cases, land area, and land ownership cases which has not been solved completely. All eight-seven (87) people inflicted on this case accounted as research’s sample. The data collected using observation, interview, questionnaire, and literature study methods. Those data were analyzed quantitatively by using tabulation system, frequency, and statictical percentage. The result shows that the village chief has quite a role by scoring average 3,63, while the influencing factors in quantity of work scores average 2,95, the quality of work scores average 3,23, dependability scores average 4,90, job knowledge scores average 3,96, creativeness scores average 2,52, cooperation scores average 4,65, initiative scores average 2,10, and finally personal quality scores average 4,77.